1986
DOI: 10.1016/s0735-1097(86)80118-8
|View full text |Cite
|
Sign up to set email alerts
|

Contrast echocardiography for evaluation of myocardial perfusion: Effects of coronary angioplasty

Abstract: Assessment of viable myocardium before and after interventional therapy has become a critical issue in modern cardiology. This report describes a new contrast echocardiographic technique using conventional two-dimensional imaging during direct intracoronary injections of small volumes (1.5 to 2.0 cc) of sonicated Renografin-76. Contrast echocardiography was performed before and after coronary angioplasty in seven patients with single vessel coronary artery disease. Before angioplasty a contrast (that is, perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…This observation is supported by a study by Lang et al 52 , who showed that the increase in the intensity of contrast is greater in the regions related to obstructed arteries that undergo angioplasty than in regions related to normal arteries due to subsequent hyperemia.…”
Section: Discussionsupporting
confidence: 61%
“…This observation is supported by a study by Lang et al 52 , who showed that the increase in the intensity of contrast is greater in the regions related to obstructed arteries that undergo angioplasty than in regions related to normal arteries due to subsequent hyperemia.…”
Section: Discussionsupporting
confidence: 61%
“…1,7 Contrast echocardiography is increasingly referred to as a technique that could potentially allow quantification 4 -6 or at least imaging of myocardial perfusion. 2,3,8,16,17 This goal, however, still remains a great challenge. 18 Although LV opacification for improved endocardial visualization is better established than perfusion imaging, it is qualitative, because there is no technique to automatically detect the endocardial border from contrast-enhanced images.…”
Section: Discussionmentioning
confidence: 99%
“…22,28 Quantification, rather than the presence or absence of the enhanced contrast, was investigated in experimental studies.24, 25 Kemper et a125 showed that the amount of contrast enhancement can provide quantitative information about myocardial blood flow. A recent clinical study20 showed that measurement of peak contrast intensity after intracoronary injections of contrast medium provides a relative index of myocardial perfusion that allows assessment of regional coronary reserve in patients with coronary artery disease.…”
Section: Reproducibility Of Resultsmentioning
confidence: 99%